Real options valuation for mining projects under dual economic uncertainty - Haque, Md Aminul (Curtin University, 2016)
Mining project cash flows are volatile, being influenced by exogenous variables. Volatility associated with commodity prices and exchange rates carry significant income risk, therefore, mining companies should practice economic risk mitigation strategies. Management should address these risks before investing by considering hedging and futures contracts strategies. DCF valuation methods are generally preferred for mining projects, typically failing to adequately capture these economic uncertainties. This thesis develops a valuation framework with new PDEs incorporating these uncertainties.